2015
DOI: 10.1016/j.virol.2014.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding proteins of Listeria monocytogenes bacteriophages A118 and P35 recognize serovar-specific teichoic acids

Abstract: Adsorption of a bacteriophage to the host requires recognition of a cell wall-associated receptor by a receptor binding protein (RBP). This recognition is specific, and high affinity binding is essential for efficient virus attachment. The molecular details of phage adsorption to the Gram-positive cell are poorly understood. We present the first description of receptor binding proteins and a tail tip structure for the siphovirus group infecting Listeria monocytogenes. The host-range determining factors in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(77 citation statements)
references
References 73 publications
5
72
0
Order By: Relevance
“…This was noted with other PTLBs and is likely the result of selective pressure to acquire different target specificities. During the course of this work, it was verified experimentally by others that A118 gp20 is the phage's RBP and that gp21 is part of the A118 baseplate (29). We show here that fully functional production of M35152-A118 also requires the presence of gp21.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…This was noted with other PTLBs and is likely the result of selective pressure to acquire different target specificities. During the course of this work, it was verified experimentally by others that A118 gp20 is the phage's RBP and that gp21 is part of the A118 baseplate (29). We show here that fully functional production of M35152-A118 also requires the presence of gp21.…”
Section: Discussionsupporting
confidence: 66%
“…Indeed, we did observe potency consistent with approximately one particle killing one target cell in the survival assay. The cellular receptor for wild-type monocins has yet to be determined; however, the receptor for phage A118 (and likely M35152-A118) is known to be teichoic acid (29). Work is under way to determine if natural monocins also utilize teichoic acids or perhaps some other cell surface structure as a receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although many studies of RBPs in phages of Gram-negative bacteria have been carried out, knowledge of RBPs in the phages of Gram-positive bacteria remains limited. To date, RBPs have been identified for Bacillus subtilis phages SPP1 and 29, Streptococcus thermophilus phages DT1 and MD4, Lactococcus lactis phages bIL67 and CHL92 of the c2 species, sk1, bIL170, and p2 of the 936 species, and TP901-1 and Tuc2009 of the P335 species, and Listeria phage A118 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Among S. aureus phages, RBPs have also been identified in Siphoviridae phage SLT and Podoviridae AHJD-like phages S24-1 and S13= (23,24).…”
mentioning
confidence: 99%
“…Remarkably, Habann et al identified that the RBPs of Listeria phage A511 and staphylococcal Twort-like phages ISP and Twort (Gp108, gp40, and gp17, respectively) are located in short tail fibers (25). Among Gram-positive bacteria, cell wall-associated carbohydrates, such as teichoic acids, are regarded as phage receptors of B. subtilis, S. aureus, and Listeria monocytogenes (15,(25)(26)(27)(28)(29). In S. aureus, siphoviruses need N-acetylglucosamine (GlcNAc) in wall teichoic acids (WTAs) for adsorption, whereas myoviruses, such as staphylococcal Twort-like phages, adsorb to the WTA backbone (27).…”
mentioning
confidence: 99%